Ecogeography of haplotype composition of Sagittaria trifolia L. (Alismataceae) : environment, space, vicariance and selective sweeps - Chen, Youhua (Acta Biologica Szegediensis, 2014)
In the present report, the relative influence of environment and space was evaluated for explaining the variation of haplotype composition of 42 populations of Sagittaria trifolia L. (Alismataceae) in China. The results showed that, neither environment nor space could explain current haplotype composition patterns of S. trifolia, and most variation in haplotype composition could not be explained. Vicariance was recognized to explain the pattern that most haplotypes (25 out of 27 ones) were rare, being found in only one or two populations of S. trifolia in China. Finally, an emerging selective sweep from increasing human activity and habitat destruction explained the dominance patterns of haplotypes 5 and 8 among populations of S. trifolia.